Chinese expert consensus on clinical practice of female fertility preservation. Issue 1 (March 2022) - Li, Wen; Chian, Ri-Cheng
Abstract : Abstract: Many female fertility preservation-related technologies have recently been developed in response to increasing demand for such treatments. To establish standard practices of female fertility preservation in China, the Chinese Maternal and Child Health Association Affiliated Fertility Preservation Professional Committee assembled specialists to construct a consensus, referring to the current clinical guidelines of some countries combined with clinical practice and expert opinions. The consensus includes two parts: (1) indications for female fertility preservation and related techniques, in which we sought to be inclusive regarding the indications for fertility preservation; and (2) practical guidance for the clinical application of the female fertility preservation technologies.